2017
DOI: 10.5194/os-13-925-2017
|View full text |Cite
|
Sign up to set email alerts
|

Forecast skill score assessment of a relocatable ocean prediction system, using a simplified objective analysis method

Abstract: Abstract. A relocatable ocean prediction system (ROPS) was employed to an observational data set which was collected in June 2014 in the waters to the west of Sardinia (western Mediterranean) in the framework of the REP14-MED experiment. The observational data, comprising more than 6000 temperature and salinity profiles from a fleet of underwater gliders and shipborne probes, were assimilated in the Regional Ocean Modeling System (ROMS), which is the heart of ROPS, and verified against independent observations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Temperature and salinity data from these gliders were assimilated into a state estimate (Todd et al, 2011a(Todd et al, , 2012Zaba et al, 2018), while velocity data were not assimilated so they could be used for verification. In the Mediterranean, Dobricic et al (2010) showed the large-scale impact of the repetition of a glider section and in particular when depth-average currents were also assimilated while Mourre and Chiggiato (2014) and Onken (2017) assimilated glider data for a forecast and verified against data from a ship survey. A state estimate of the tropical Pacific (Verdy et al, 2017) was verified against withheld glider observations on either side of the Pacific basin.…”
Section: Moving From the Regional To The Globalmentioning
confidence: 92%
“…Temperature and salinity data from these gliders were assimilated into a state estimate (Todd et al, 2011a(Todd et al, , 2012Zaba et al, 2018), while velocity data were not assimilated so they could be used for verification. In the Mediterranean, Dobricic et al (2010) showed the large-scale impact of the repetition of a glider section and in particular when depth-average currents were also assimilated while Mourre and Chiggiato (2014) and Onken (2017) assimilated glider data for a forecast and verified against data from a ship survey. A state estimate of the tropical Pacific (Verdy et al, 2017) was verified against withheld glider observations on either side of the Pacific basin.…”
Section: Moving From the Regional To The Globalmentioning
confidence: 92%
“…The closer the absolute values of the CCs and WSSs are to 1, the better the results of the simulation. The performance levels of WSS were categorized as: >0.2, some credibility; >0.5, high credibility [67]. The model results for water levels showed excellent agreement with the field data (Figure S1I).…”
Section: Model Validationmentioning
confidence: 68%
“…Concerning operational forecasting, a relocatable ocean prediction system was applied in hindcast mode to the survey data (Onken, 2017a). More than 6000 temperature and salinity profiles originating from the glider fleet and shipborne CTD probes were assimilated, and the forecasts were verified against observations from the ScanFish tows (Fig.…”
Section: Discussionmentioning
confidence: 99%